THE STRUGGLE OF AMERICAN MINORITIES DURING GREAT DEPRESSION IN JOHN STEINBECK’S OF MICE AND MEN - MUSAFAâ€™AT, KHABIB (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: American minorities, struggle, Great Depression, MarxistNovella is one of fictions which the event happens in the story does not really happen in reality. But since it is a literary work, it may depict the real condition of an era. In the era of Great Depression, it is known that United States of America suffered from big economic crisis. In this study a novella entitled Of Mice and Men is chosen as the object of the study. This study is purposed to identify about how the struggle of America minorities during Great Depression.This study uses Marxist theory as the main tool of analyzing. In the process of the research, the theory of Marxist is correlated to the concept of minority also the concept of equality. The data is collected from the narration, characterization, and the dialogue of the characters. The procedure of analysis is started by collecting data, interpreting and analyzing related object of the study in the story, and drawing the conclusion.The result of the study shows about the struggle of American minorities during Great Depression. The struggle can be found by classifying the object of the study based on their factors of minority. There are five classes found in the research: the struggle of minority group in terms of (1) economic, (2) race, (3) age, (4) sex, and (5) disability. Basically, every group struggles to get equality based on their terms of minority, but the analysis shows that some groups intend to get equality of respect as their main aim.